Delivering sustainable growth in Africa : African farmers and firms in a changing world - Fukunishi, Takahiro; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The purpose of this book is to fill the lack of micro evidences on a structural change of African producers. By collecting studies on single industries, we attempt to demonstrate firms' and farmers' responses to the recent economic trend such as growth of demand, emergence of FDI and improvement in infrastructure.
Keywords: Agriculture -- Economic aspects -- Africa, Sub-Saharan.; Sustainable agriculture -- Africa, Sub-Saharan.; Economic development -- Africa, Sub-Saharan -- History -- 21st century